2018
DOI: 10.22225/jr.4.1.526.70-74
|View full text |Cite
|
Sign up to set email alerts
|

Politeness of Verbal and Non-Verbal Directive Speech Acts in the Tenth Grade Students’ Learning Process of Negeri 1 Mataram

Abstract: This research aims at knowing: (1) the realization of politeness of verbal and non-verbal directive speech acts of students, (2) deviations on politeness principles of students’ directive speech acts, and (3) the determining factors to the politeness and non-politeness of verbal and non-verbal directive speech acts for the Tenth Grade students of SMA Negeri 1 Mataram in the process of learning in the classroom. Research subjects in this study were the teachers who taught Indonesian, English, Economics, History… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Further more Leech stated that the other way to recognize the politeness scale is by looking at the content of the same utterances by using various indirect speech acts [13]. What is discussed above is in accordance with what is said by Lindayana, et.al [14] who stated that speaking activity is very necessary to assume the principle of courtesy. Language politeness can be seen in the process of directive speech acts done in the learning process.…”
Section: The Use Of Interrogative Sentencesupporting
confidence: 72%
“…Further more Leech stated that the other way to recognize the politeness scale is by looking at the content of the same utterances by using various indirect speech acts [13]. What is discussed above is in accordance with what is said by Lindayana, et.al [14] who stated that speaking activity is very necessary to assume the principle of courtesy. Language politeness can be seen in the process of directive speech acts done in the learning process.…”
Section: The Use Of Interrogative Sentencesupporting
confidence: 72%
“…It is simple to understand because the illocutionary force has the same structure and meaning as the locutionary act. The verbal act can be seen from the use of the speech act used by the speaker (Lindayana et al, 2018). The characteristic is that speakers usually use directive speech, such as commanding and asking.…”
Section: Verbal Actmentioning
confidence: 99%
“…Directive speech acts are speech acts that threaten the "face" (self-image of the doer) so that many researchers are called to teach it [2]. People who have done research politeness multiethnic learner is Ali (2011) [3], Masfufah (2012) [4], Ardhiarta (2013) [5], Afriansyah (2016) [6], Arta (2016) [7], Noor dan Prayitno (2016) [8], Abdurrahman (2017) [9], Musyawir (2017) [10], Nurjanah (2017) [11], Sahlullah (2017) [12], Alika (2011) [13], Kurniadi, Hilaliyah (2018) [14], Cahyaningrum (2011) [15], Febriadina (2017) [16], Jamaluddin (2018) [17], Widiadnya, Seken, Santosa (2018) [18], Lindayana, Arifuddin, Mandala (2018) [19], Cahyaningrum, Andayani dan Setiawan (2018) [20], Abdurrahman dan Manaf (2018) [21]. Ali (2011) research is the politeness imperative interaction son Madrasah Aliyah students of Class X was typical [9].…”
Section: Introductionmentioning
confidence: 99%
“…Widiadnya,Seken, and Santosa (2018) found that communications were polite between teachers and students make the learning process efficient, between teachers and students mutual respect , cooperation between teachers and students well , there is no compulsion in the learning process [18]. Lindayana, Arifuddin, Mandala (2018) conducted a study where the results of the research were in the learning process , tended to use the strategy of politeness to speak frankly or directly with certain pleasantries [19]. Cahyaningrum, Andayani and Setiawan (2018) found Surakarta students used a strategy tells different in me response to an act of speech are the same [20].…”
Section: Introductionmentioning
confidence: 99%